Marine resources and their value in Kadavu, Fiji - Simon Harding; Kalisiana Marama; Annette Breckwoldt; Ulamila Matairakula; Elodie Fache (Ambio, 2022)
Recognition of the multiple types of value of marine resources is crucial to help design locally meaningful and sustainable management approaches for marine and coastal habitats. There is a lack of information on the amount of living marine resources harvested by coastal communities in many Pacific Island Countries and Territories (PICTs), as well as on their economic and non-economic value. This paper explores the monetary, subsistence, and sociocultural value of selected marine resources (finfish and invertebrates) in Kadavu province, Fiji, based on a household survey and semi-structured interviews conducted in 2019 within one specific district. The paper provides estimates of the annual catch and monetary value of marine resources harvested by local communities at both the district and provincial levels, derived from catch and effort information collected from fishers and gleaners in situ. It also highlights the importance of integrating the sociocultural significance of marine resources into future value assessments.